Alcohol use and bipolar disorders: Risk factors associated with their co-occurrence and sequence of onsets. (1st October 2017) - Azorin, Jean-Michel; Perret, Léa C.; Fakra, Eric; Tassy, Sébastien; Simon, Nicolas; Adida, Marc; Belzeaux, Raoul
Highlights: Little is known about the sequence of onsets of alcohol use and bipolar disorders. Rates of 6.6% were found in the alcohol first group (AUD-BD). Rates of 45.8% were found in the bipolar first group (BD-AUD). AUD-BD was associated with sedative abuse and depressive polarity at onset. BD-AUD was associated with stimulant abuse and manic polarity at onset. Abstract: Background: Little is known about the sequence of onsets in patients affected by comorbid alcohol use and bipolar disorder. This study examines the risk factors associated with their co-occurrence and order of onset. Method: The demographic, clinical, and temperament characteristics as well as the course of illness were analyzed within our sample of 1090 DSM-IV bipolar I manic patients. Our sample was categorized according to the presence of comorbid alcohol use disorder and the sequence of onsets of bipolar and alcohol use disorders i.e., alcohol first (AUD-BD) and bipolar first (BD-AUD). Results: Regression analyses revealed that alcohol use disorder (52.5%) was associated with the male gender, additional substance use disorders, as well as an irritable and a hyperthymic temperament. The AUD-BD group (6.6%) was older than the BD-AUD group (45.8%) and showed higher rates of comorbid sedative use, organic, and anxiety disorders with higher levels of irritable temperament, and a bipolar subtype characterized by depressive polarity at onset. The BD-AUD group had high levels of hyperthymic temperament with higher rates of comorbid stimulant use disorder and a manic polarity at onset. Conclusions: In the AUD-BD group, alcohol might have been used to reduce stress and tension caused by the presence of an irritable temperament as well as anxious and organic disorders, leading to first depressive episode. In the BD-AUD group, stimulant use might have triggered the first manic episode, and alcohol abuse result from mania severity.